2021
DOI: 10.3346/jkms.2021.36.e248
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19-related Mortality and 30-Day and 60-Day Survival Probabilities Using a Nomogram

Abstract: Background Prediction of mortality in patients with coronavirus disease 2019 (COVID-19) is a key to improving the clinical outcomes, considering that the COVID-19 pandemic has led to the collapse of healthcare systems in many regions worldwide. This study aimed to identify the factors associated with COVID-19 mortality and to develop a nomogram for predicting mortality using clinical parameters and underlying diseases. Methods This study was performed in 5,626 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Fifty-five studies aimed to exclusively predict in-hospital mortality [ 2 , 11 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 ], while thirteen reported on combined outcome...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-five studies aimed to exclusively predict in-hospital mortality [ 2 , 11 , 14 , 15 , 16 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 ], while thirteen reported on combined outcome...…”
Section: Resultsmentioning
confidence: 99%
“…Study setting included general population from database sources [ 19 , 23 , 49 , 58 , 68 , 71 ], clinical records from series of patients admitted to hospital [ 2 , 11 , 12 , 14 , 16 , 17 , 18 , 20 , 21 , 22 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , 6...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis study, it was shown that comorbid diseases such as hypertension, diabetes mellitus, cardiovascular disease, and respiratory diseases can have a significant effect on the prognosis of COVID-19 [15]. Moon et al [25] reported that elderly age can influence the clinical course of COVID-19 and COVID-19-related mortality through immune aging or high prevalence of comorbid diseases. A study of adult patients with COVID-19 in England and Wales [26] showed that hypertension, dementia, chronic lung disease, and diabetes mellitus were associated with death.…”
Section: Discussionmentioning
confidence: 99%
“…21 Co-medications were included, and sex was added based on recent findings. 32 33 34 To confirm the consistency of the results, we performed sensitivity analyses by changing the covariates included in the PS estimation model, changing the matching method, and adding covariates in the multivariable logistic regression model of analyzing matching data.…”
Section: Methodsmentioning
confidence: 99%